Fundamentals of management - Ricky W. Griffin (Houghton Mifflin, 2008)
This skills-based text from respected author Ricky Griffin gives instructors the flexibility to integrate their own cases, exercises, and projects while continuing to provide them with a strong theoretical framework. Chapters are organized according to a strong pedagogy, featuring learning objectives, a chapter outline, a First Things First opening vignette, boldface key terms, a summary of key points, questions for review, questions for analysis, end of chapter exercises, and an end-of-the-chapter case with questions